Sosialisasi Peran Pemuda dalam Meningkatkan Pertumbuhan Ekonomi di Gereja GPDI Eben Haezer Jayapura - Richard Patty; Pisi Bethania Titalessy; Stephanny Inagama Timisela; Agustina Ester Antoh; Herlina Irianti Mulyono; Zulhendri Zulhendri (Syntax Corporation Indonesia, 2024)
This community service activity aims to increase youth understanding of their important role in advancing the local, regional and national economy. This socialization was held at the GPdI Eben Haezer Jayapura Church and involved church youth as participants. The methods used include preparation, delivery of material, as well as discussions and questions and answers. The results of this activity show an increase in youth understanding of their role in economic growth. The participants also gained knowledge about the concept of economic growth, the role of youth, and ways to develop their potential in creating jobs. This activity succeeded in involving the active participation of participants and increasing their understanding of the importance of the contribution of the younger generation to the economy. However, there are shortcomings in the limited duration of activities and the scope of participants only from one community.